2020
DOI: 10.2147/copd.s230072
|View full text |Cite
|
Sign up to set email alerts
|

<p>Multi-morbidities are Not a Driving Factor for an Increase of COPD-Related 30-Day Readmission Risk</p>

Abstract: Background and Objective: Chronic obstructive pulmonary disease (COPD) is the third leading cause of death in the United States. COPD is expensive to treat, whereas the quality of care is difficult to evaluate due to the high prevalence of multi-morbidity among COPD patients. In the US, the Hospital Readmissions Reduction Program (HRRP) was initiated by the Centers for Medicare and Medicaid Services to penalize hospitals for excessive 30-day readmission rates for six diseases, including COPD. This study examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…In addition, the more the number of combined metabolic abnormalities, the higher the readmission rate. If metabolic abnormality was regarded as comorbidity, consistent with our view, past studies indicated that the readmission risk would raise as the number of comorbidities increased in patients with COPD who combined with comorbidities ( Roberts et al, 2011 ; Lin et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…In addition, the more the number of combined metabolic abnormalities, the higher the readmission rate. If metabolic abnormality was regarded as comorbidity, consistent with our view, past studies indicated that the readmission risk would raise as the number of comorbidities increased in patients with COPD who combined with comorbidities ( Roberts et al, 2011 ; Lin et al, 2020 ).…”
Section: Discussionsupporting
confidence: 74%
“…Patients with COPD are known to have a higher prevalence of comorbidities that often include HF, CAD, DM, and PAD, amongst others 1 . The decreased post‐LVAD complications in COPD patients with comorbidities goes along with the finding of a recent study that shows a paradoxical lower risk of 30‐day readmission in COPD patients with comorbidities compared to COPD patients without comorbidity 33 . One of the major complications of LVAD is postoperative neurological events including both ischemic and hemorrhagic strokes 34‐37 .…”
Section: Discussionmentioning
confidence: 95%
“…1 The decreased post-LVAD complications in COPD patients with comorbidities goes along with the finding of a recent study that shows a paradoxical lower risk of 30-day readmission in COPD patients with comorbidities compared to COPD patients without comorbidity. 33 One of the major complications of LVAD is postoperative neurological events including both ischemic and hemorrhagic strokes. [34][35][36][37] COPD was associated with increased risk for stroke post-LVAD implantation in a small study of 200 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies published between 2015-2020, the most widely examined risk factors included a variety of comorbidity measures such as comorbidities themselves, the number of comorbidities, comorbidity burden, and the Charlson Comorbidity Index (CCI). Specifically, nine of these articles identified comorbidities as a risk factor for increasing readmission among COPD patients (34)(35)(36)(37)(38)(39)(40)(41)(42), one found that the number of comorbidities was a risk factor for decreasing the risk of readmission (43), and another found mixed results relative to comorbidities-that is that some comorbidities such as heart disease decreased readmission risks while others like lung cancer increased readmission risks (44). Within studies examining comorbidities, four examined CCI as a risk factor, among others, to readmission.…”
Section: Individual-level Risk Factorsmentioning
confidence: 99%